Pengaruh Double Chamfer Terhadap Kekuatan Tarik Dan Struktur Mikro Pada Hasil Sambungan Las Gesek Al 6061 - Andi Priambudi; Iman Dirja; Rizal Hanifi (Universitas Muhammadiyah Yogyakarta, 2024)
Aluminum, with a thermal conductivity close to 2/3 that of copper, can utilize friction welding effectively. Chamfer angles improve the welding quality by increasing the generated heat, resulting in higher mechanical properties. This study investigates the impact of chamfer angles (15°, 30°, and 45°) on the microstructure and tensile strength of friction-welded Al 6061 under conditions of 1600 rpm rotation, 50 MPa forging pressure, 20 MPa friction pressure, and 45 seconds of welding time. Microstructure and tensile strength tests were conducted on three specimens for each chamfer angle. Results show that increased friction time, friction pressure, and forging pressure lead to greater material loss due to flash formation. Microstructure analysis revealed that chamfer angles of 30° and 45° achieved better welding at the interface due to sufficient heat generation. In the heat-affected zone (HAZ), all angles (15°, 30°, and 45°) showed phase structure changes, with broader and more uniform Mg2Si and Fe3SiAl12 phases, attributed to the cooling process and relatively low heat. Tensile testing showed the highest tensile strength (177.9 MPa) and strain (6.42%) for the 30° chamfer angle, outperforming the 15° and 45° angles. The smallest strain (3.72%) was observed in the 15° chamfer angle, indicating the significant influence of chamfer geometry on friction welding outcomes.